Observations on the usefulness of null hypothesis testing [corrected] [published erratum appears in J THEORY CONSTRUCT TEST 1999 Fall; 3(2): 37]. - Marshall DD (Journal of Theory Construction & Testing)
Nursing has long relied on classical null hypothesis significance testing in establishing effects within the broad enterprise of theory testing. The usefulness of significance testing has debated throughout its history, and the debate has distilled to vociferous proclamations that the null hypothesis, H[0], and the p-value given by significance testing are inept and scientifically irrelevant. Serious intentions to eliminate H[0] and traditional H[0] testing have appeared, with recommendations for focus on effect size and clinical relevance instead. Careful scrutiny reveals uncertainties in these indictments and in exclusive attention to effect size. Another criticism is about the convention of rejecting or not rejecting H[0] based on p (.05 regardless of effect size. This reproach has meritorious implications for practice. The specific incriminations against H[0] testing must be examined before the debate is considered settled and nursing science joins in doing away with significance testing. While clinical relevance of an effect is a crucial aspect of asserted support for a research hypothesis, and observed sample effect should also be considered in view of addressing the sampling error explanation of observed effects, while judgements about 'significance' are subjective convictions.